ТЕОРЕТИЧЕСКОЕ РАСПРЕДЕЛЕНИЕ КОНЦЕНТРАЦИИ ГАЛЛИЯ И СУРЬМЫ ЭЛЕМЕНТОВ ЛЕГИРОВАННОГО, ДИФФУЗИОННЫМ СПОСОБОМ В КРЕМНИИ - Исаков, Б.О. (SCIENCE and SOCIETY, 2022)
In this work is theoretically investigated using the MathCad program, a mathematical model for the distribution of the concentrations of the elements of gallium and antimony doped by diffusion into silicon. The essence of theoretical calculations and mathematical modeling of the diffusion process is not to conduct experiments in vain, to determine in advance the depth of penetration of impurity atoms into silicon before diffusion occurs, and to plan experiments and increase the reliability of the results.
Keywords: silicon; gallium; antimony; concentration; diffusion; diffusion coefficient